Detection and Quantitation of Aflatoxin for the Diagnosis of Aspergillus flavus - Shrestha, Geeta Rajbhandari; Mridha, Amin Udhin (Nepal Journal of Biotechnology, 2015)
Aflatoxins are the potent mycotoxins produced by Aspergillus flavus, which is hepatotoxic causing hepatocellular carcinoma. A. flavus produces sufficient amount of Aflatoxin B1 under favourable environments. Inhalation of spores and use of Aflatoxin B1, contaminated food by Aspergillus spp., could transfuse the toxins in the blood streams. The presence of these toxins in body fluid can be detected by immunological assays and which provides an effective technique for the diagnosis of the disease caused by A. flavus. Aflatoxins producing strain of A. flavus were screened in Aflatoxin Producing Medium. Production of Aflatoxin B1 by A. flavus was studied in different parameters such as incubation periods, temperatures, pH variations, sucrose concentration in Yeast Extract Sucrose medium and different natural media such as par-boiled rice, corn and groundnuts. The detection of toxins was done by TLC using silica gel (Merk) coated plates and confirmative test was done by Association of Official Analytical Chemists (AOAC) method. Presence and quantization was done by Enzyme Linked Immunosorbent Assay (ELISA) technique. Highest amount of Aflatoxin B1 was reported 68.56 ng/ml by ELISA in synthetic medium (Yeast Extract Sucrose) with 2% sucrose, pH 5.5, on 14th days of incubation, at 28±1°C (p-value 0.05). Similarly, highest amount was recorded in groundnuts (121.20ng/g) by ELISA and (500ng/kg) by TLC methods. ELISA is one of the most efficient methods used for detection and diagnosis of human diseases cause due to exposure of Aflatoxin B1 and A. flavus. Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 6-9